The Association between Family Socioeconomic Status and Children's Digital Literacy: The Explanatory Role of Parental Mediation - Xiaohan Shi; Jing He; Gengfeng Niu (MDPI AG, 2024)
In the current information society, digital literacy has become an indispensable part of individuals' overall literacy. Thus, investigating the factors influencing digital literacy is of theoretical and practical significance, especially for developing children. Against this background, the present study examined the association between family socioeconomic status and children's digital literacy and the mediating roles of active and restrictive parental internet mediation in this association. A total of 1050 Chinese students ranging from Grades 4 to 8 completed questionnaires in their classrooms. Regression-based analyses showed that (1) family socioeconomic status was positively associated with digital literacy and (2) active parental mediation could significantly mediate this relationship, but the mediating effect of restrictive parental mediation was insignificant. This research not only deepens our understanding of the factors affecting digital literacy but also provides an empirical reference point for interventions to improve children's digital literacy.